METHODOLOGICAL AND METHODICAL FOUNDATIONS EVALUATION OF EFFECTIVENESS OF INVESTMENT PROJECTS IN SCIENTIFIC RESEARCH - G. Ryazanova; A. Sazanova (Вестник университета)
The authors substantiate the features of investment projects in research and development; Explore methodological approaches to assessing the effectiveness of investment projects that have evolved in modern domestic and foreign economic science. Additionally identify the advantages and disadvantages of existing methods and substantiate the need for their improvement.